THE IMPACT OF INNOVATION AND TECHNOLOGY ON TRANSFORMING MARKETING STRATEGIES AND ACHIEVING SUSTAINABLE SUCCESS - Omar Karim Kazem Hussein; Shaima Mahmoud Taraf Jawad (Galaxy International Interdisciplinary Research Journal, 2024)
The study aimed to determine the impact of marketing innovation and technology on the marketing strategy and sustainable success of Asia cell, an Iraqi telecommunication company. A descriptive survey method was used, and questionnaires were distributed to the study sample, which consisted of (260) employees of Asia Cell, an Iraqi telecommunication company. After (250) questionnaires were retrieved and deleted, (6) questionnaires contained missing values, (4)) questionnaires were not suitable for analysis due to the inclusion of outliers, and (250) final total number was resolved. The study found that companies with high levels of marketing innovation had an arithmetic mean of (4.133) and high levels. In contrast, companies with high levels of technology had an arithmetic mean of (4.208) and high levels of marketing strategy and sustainable success. The arithmetic means of (4.087) was obtained with a high degree and a high degree. The level of marketing strategy reached a high arithmetic mean of (3.981) but was lower than the level of sustainable success. The study concluded that there is a positive correlation between innovative marketing and technology and marketing strategy and sustainable success. In addition, the study also highlights the importance of considering innovation and technology when improving the marketing strategy of telecommunication companies.